2012
DOI: 10.1673/031.012.2001
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Diversity of Soil Arthropods in the Olive Grove Ecosystem

Abstract: Arthropods are part of important functional groups in soil food webs. Recognizing these arthropods and understanding their function in the ecosystem as well as when they are active is essential to understanding their roles. In the present work, the abundance and diversity of soil arthropods is examined in olive groves in the northeast region of Portugal during the spring. Five classes of arthropods were found: Chilopoda, Malacostraca, Entognatha, Insecta, and Arachnida. Captures were numerically dominated by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 31 publications
2
39
1
2
Order By: Relevance
“…) but, during winter, its activity was reduced, remaining in nests, due to low temperatures. Gonçalves and Pereira () also observed lower numbers of Formicidae in early spring. The community of formicids was mainly composed by the species M. barbarus and T. nigerrimum that have been previously referred in other works concerning the same ecosystem (Morris and Campos ; Santos et al.…”
Section: Discussionmentioning
confidence: 84%
“…) but, during winter, its activity was reduced, remaining in nests, due to low temperatures. Gonçalves and Pereira () also observed lower numbers of Formicidae in early spring. The community of formicids was mainly composed by the species M. barbarus and T. nigerrimum that have been previously referred in other works concerning the same ecosystem (Morris and Campos ; Santos et al.…”
Section: Discussionmentioning
confidence: 84%
“…Amazonicum) também encontraram maior abundância das ordens de insetos Hymenoptera e Coleoptera. Dentro dos hymenópteros amostrados neste estudo houve a maior ocorrência de indivíduos da família Formicidae nos diferentes agroecossistemas, corroborando com os trabalhos realizados por Moço et al (2005), Santos et al (2007), e Gonçalves & Pereira (2012). As formigas compreendem um terço do total da biomassa de insetos das florestas brasileiras, além disso, elas são altamente ativas no solo, o que facilita a sua coleta (Harada et al, 2013).…”
Section: Introductionunclassified
“…This winter peak could be attributed to the high seasonal humidity, favouring the specific taxa. Gonçalves and Pereira (2012) found Collembola to be the most abundant in the soil of olive orchards, justifying accordingly their findings by seasonality of measurements and environmental conditions. No significant differences of Collembola catches appeared between agroecological zones.…”
Section: Fig 1 Rank Abundance Curves Of Hilly (X) and Plain Agroecomentioning
confidence: 68%
“…Several studies have showed that predatory soil arthropod community can inflict mortality on the Tephritidae pupae (Bateman 1972, Cavalloro and Delrio 1976, Bigler et al 1986, Orsini et al 2007). Typical potential predators of the Tephritidae pupae are taxa such as Araneae, Carabidae, Staphylinidae, Formicidae and Opiliones (Bateman 1972, Cavalloro and Delrio 1976, Wong et al 1984, Bigler et al 1986, Allen and Hagley 1990, Thomas 1995, Hennessey 1997, Hodgson et al 1998, Urbaneja et al 2006, Gonçalves and Pereira 2012.…”
Section: Introductionmentioning
confidence: 99%